2018
DOI: 10.1111/bcp.13623
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcome instruments that evaluate adherence behaviours in adults with asthma: a systematic review of measurement properties

Abstract: Our results highlighted the need to conduct further high-quality studies to evaluate the reliability, validity and responsiveness of the available PROs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A number of previous studies have been conducted to validate PROMs on medication adherence [ 12 , 15 - 17 ], and a previous systematic review found 14 PROMs that assessed adherence to inhaled asthma maintenance medication alone [ 18 ]. However, to date, there is no comprehensive review that summarizes the psychometric properties of PROMs for medication adherence, which is essential to guide the selection of suitable PROMs to evaluate medication adherence in patients.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have been conducted to validate PROMs on medication adherence [ 12 , 15 - 17 ], and a previous systematic review found 14 PROMs that assessed adherence to inhaled asthma maintenance medication alone [ 18 ]. However, to date, there is no comprehensive review that summarizes the psychometric properties of PROMs for medication adherence, which is essential to guide the selection of suitable PROMs to evaluate medication adherence in patients.…”
Section: Introductionmentioning
confidence: 99%
“…PROMs are insufficient at tracking asthma medication adherence compared with objective measures, such as prescription refill rates. In a systematic review of 14 PROMs designed to evaluate inhaler medication adherence in adults with asthma, there was no evidence that they could detect changes in adherence scores over time [33]. Thus, these tools cannot fully distinguish whether uncontrolled symptoms are caused by medication nonadherence versus truly refractory disease.…”
Section: Medication Adherencementioning
confidence: 99%
“…A recent systematic review of patient-reported outcome instruments to evaluate adherence in adults with asthma concluded the evidence was mixed or unknown regarding the reliability and validity of currently available tools, but that there was no evidence of the responsiveness of any available instrument, and no recommendation could be made regarding the use of a particular tool in routine care or in research settings [ 35 ].…”
Section: Measuring and Identifying Non-adherencementioning
confidence: 99%